DESIGN AND BUILD AN AUTOMATIC COFFEE ROASTING MACHINE USING PLC AND HMI WITH PID METHOD - Achmad Ilyas Ath Thaariq; Akhmad - Fahruzi (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
ABSTRACT Coffee is a plantation product that has economic value and plays a role as a source of foreign exchange for the country. The quality of coffee depends much on its handling during the harvest and post-harvest processes. Proper management in the harvest and post-harvest processes can produce good quality coffee. Coffee beans have so great differences that require skill and experience in carrying out the roasting process based on the consumer demand. Therefore, a multi-step system was created in a roasting process by varying the roasting temperature and time variables. This study aimed to analyze the working system of an automatic coffee roaster machine to optimize temperature using HMI and PLC. PID method was applied as the control system for the temperature of the combustion chamber of the coffee roaster machine to the desired temperature during the roasting process. The testing of the type K thermocouple temperature sensor worked quite well with an error average of the temperature reading of 1.51%, whereas the error value of the stepper motor movement of the system gained an average of 0.9%. The multi-step coffee roasting system was tested as follows: the first stage at the set point temperature of 100oC for 8 minutes, the second stage at the set point temperature of 120oC for 7 minutes, and the final stage at the set point temperature of 125oC for 7 minutes, or the total test time of 22 minutes. The results indicated that the multi-step coffee roasting test obtained an average overshoot error of 1.78% and an average settling time error of 0.74%. Overall, the temperature control system using the PID method for the coffee roaster combustion chamber could work according to the specified set point.